Peer-to-Peer Learning (Peerogy) in Electronics Practice Learning: Adaptation of Andragogy and Heutagogy in Vocational High Schools - Satriyo Agung Dewanto; Bekti Wulandari; Muhammad Izzuddin Mahali; Bonita Destiana; Fitriani Mediastuti (LP. Ma'arif Janggan Magetan, 2025)
Vocational electronics education requires learners to integrate theoretical knowledge with practical experience, yet traditional teacher-centered instruction often limits autonomy, collaboration, and meaningful engagement, forming the background of this study. The purpose of the study is to examine how peer-to-peer learning (peerogy) can operationalize andragogical and heutagogical principles in electronics practicum activities. This study employed an embedded case study design at a vocational high school in Yogyakarta. From a broader macro-population of 504 eleventh-grade electronics students and 21 teachers, a focal class of 24 students (structured into six collaborative project teams) was selected via purposive sampling for in-depth qualitative observation, interviews, and artifact analysis across six practicum sessions. The study introduces the Peer-Mediated Pedagogy-Andragogy-Heutagogy (PAH) Transition Model to address dual-layer friction (hardware failure vs. software debugging) in Cyber-Physical Systems instruction. The results show that peerogy facilitates active knowledge sharing, collaborative problem-solving, and reflective practice, supporting the andragogical focus on experience-based and problem-centered learning, while students also demonstrated heutagogical traits such as setting self-determined goals, making independent decisions during practicum work, and evaluating their outcomes autonomously. The conclusions indicate that integrating peerogy with andragogy and heutagogy enhances learner autonomy, critical reflection, and collaborative competence, offering an effective instructional framework for cultivating adaptive, self-directed learners required in the current digital and industrial era.